Incidence of patulin in fruits and fruit juices marketed in Campinas, Brazil - Sylos, Célia Maria de [UNESP]; Rodriguez-Amaya, Delia B. (Taylor & Francis, 1999)
One hundred and eleven samples of processed fruit juices (apple, grape, pineapple, papaya, guava, banana and mango) and 38 samples of sound fruits (apple, papaya, mango, pear and peach) produced and marketed in Brazil, were analysed for patulin by HPLC. Only one out of 30 samples of apple juice was found positive at 17 μg/l. Patulin was not detected in the other foodstuffs. It was found in 14 samples of spoiled fruit samples of apple (150-267 μg/kg), pear (134-245 μg/kg) and peach (92-174 μg/kg). Confirmation of the identity of patulin was based on the UV spectrum obtained by the HPLC diode array detector, compared with that of standard patulin, TLC developed by several solvent systems and sprayed with 3-methyl-2-benzothiazolinone hydrazone, and by acetylation with acetic anhydride.
Keywords: Contamination; Fruit juices; Fruits; Mycotoxin; Patulin; patulin; Brazil; food contamination; fruit; fruit juice; high performance liquid chromatography; priority journal; thin layer chromatography; Beverages; Carcinogens; Chromatography, High Pressure Liquid; Food Contamination; Fruit; Humans; Rosales